De novo Whole-Genome Assembly of Moringa oleifera Helps Identify Genes Regulating Drought Stress Tolerance - Shyamli, P Sushree; Pradhan, Seema; Panda, Mitrabinda; Parida, Ajay (Frontiers in Plant Science, 2021)
Abiotic stresses, especially drought stress, are responsible for heavy losses in productivity, which in turn, poses an imminent threat for future food security. Understanding plants’ response to abiotic stress at the molecular level is crucially important for mitigating the impacts of climate change. Moringa oleifera is an important multipurpose plant with medicinal and nutritional properties and with an ability to grow in low water conditions, which makes the species an ideal candidate to study the regulatory mechanisms that modulate drought tolerance and its possible use in agroforestry system. In the present communication, we report WGS of this species and assemble about 90% of the genome of M. oleifera var. Bhagya into 915 scaffolds with a N50 value of 4.7Mb and predicted 32,062 putative protein coding genes. After annotating the genome, we have chosen to study the Heat shock transcription factor (HSFs) family of genes to analyse their role in drought tolerance in M. oleifera. We predicted a total of 21 HSFs in the M. oleifera genome and carried out phylogenetic analyses, motif identification, analysis of gene duplication events and differential expression of the HSF coding genes in M. oleifera. Our analysis reveals that members of the HSF family have an important role in the plant’s response to abiotic stress and are viable candidates for further characterisation.